Experimental and elastoplastic model investigation on brittle-ductile transition and hydro-mechanical behaviors of cement mortar. (10th November 2019) - Wang, Susheng; Xu, Weiya; Yang, Lanlan
Highlights: Performed brittle-ductile transition and hydromechanical tests on cement mortar. Proposed a novelty model to capture the brittle-ductile transition behavior. Described the hydromechanical behaviors based on the effective stress principle. Deduced the numerical integration formation of the model in details. Abstract: In this study, a series of tests of cement mortar were conducted. The aim is to investigate brittle-ductile transition and hydromechanical behaviors of cement mortar. These results indicate that cement mortar is brittle failure under low confining pressure, while it is ductile under high confining pressure. The strength is weakened while the deformation increases under the effect of the hydromechanical coupling. The local shear failure is in the brittle regime while diffuse compaction without obvious macrocrack is in the ductile regime. Based on experimental results, a novelty elastoplastic model is proposed for describing the brittle-ductile transition behavior and the hydromechanical effect of cement mortar. The model parameters can be directly and indirectly determined by the experimental results. The numerical integration formation of the model adopted backward Euler iteration algorithm is deduced in detail. Finally, the capability of the model in describing the mechanical behaviors of cement mortar is demonstrated by comparing numerical simulation and test results.